Design and Implementation of Smart Farm Protector from Wild Animals and Human Intruders Using LDR Powered by Solar Power - Nayana D. K., Vanishree D. V., Gagana V., Sushma S., Swathi Subhash (International Journal of Modern Agriculture, 2021)
Surveillance against vandalization plays a major role in many fields. It assists us to track a particular region and avoid theft. In the case of croplands or cultivated lands, monitoring is essential to inhibit unauthorized person from accessing to the territory along with safeguarding the region from wild animals. This project provides a smart solution to resolve this problem by using Raspberry pi. This method includes protection from theft and surveillance. To ensure protection this device differentiate between trespasser and an authorized person utilizing RFID. When such intrusions occur, camera installed in the entrance of the field captures an image of the intruder, field owner will automatically get an alert mail. Thus, ensures that only owner can enter the farmland. Each detectors and elements are connected to the Raspberry pi board. Here solar panel is used to provide the required power and hence reduces the cost. This project proposes a sustainable technological system as an end product that can be extremely valuable for farmers, as it avoids the damage to the harvest and improves agricultural production, also safeguards the territory from intruders and wild animals. In addition soil moist sensor is used to prevent over irrigation and hence saves water. Temperature and humidity of soil are continuously monitored and these readings are sent to owner to take action accordingly.